Hands-On Job Interview Training for SMK Muhammadiyah Pelaihari: Sharing Etiquette and Practice through Role-Play - Dina Rafidiyah; Yansyah Yansyah (Perkumpulan Peneliti Ilmu Lingkungan - Green Visioneers, 2019)
Dealing with a first-time job interview will always make us nervous. A thorough preparation and knowledge about it is necessary to widen the chance to get the job. This paper shares the process and result of a hands-on job interview training given to a vocational high school student, SMK Muhammadiyah Pelaihari. Forty students joined the training, which was intended to equip them with knowledge and skills to face a job interview in English. The training was conducted in form of a role play so the students can see and experience by themselves the process of a job interview. Observation and interview were carried out during and after the training, so the data related to the result and students’ opinion can be gathered. Most of the students were actively participated and happy with this kind of training because in the future they are sure that this skill is beneficial.